Geology of the Patharkhola Area, Almora District, Uttarakhand (India): With Special Reference to the Lithology and Field Relation - Rana, Haritabh; Thomas, Harel (Bulletin of the Department of Geology, 2018)
The Patharkhola area (longitude 79°09’E to 79°17’56’’E and latitude 29°47’42’’N to 29°56’69’’N) covering an area of about 125 square Kms situated in Almora District, Uttarakhand forming a part of the Almora Nappe has been selected for the detailed geological mapping at an scale of 2 cm equal to 1 Km. The rocks mainly include phyllites, schists and gneisses forming an anticlinal structure showing phyllites in the NW, S to SW and in the western part of the area, while the schists occur in the folded outcrop pattern in between both the limbs of the fold and the gneisses occur in the core of the fold. Although thin quartzitic bands has also been noticed interbedded with phyllites and schists. Several transverse faults have been noticed in the area under investigation which has been demarcated in the map. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 1-6